Working in a Conventional Bank with a MaqÄshid SyarÄ«ah Perspective - Muhammad Irkham Firdaus; Nuarisa, Risma Hafida; Puti Aqilla Asary Arief; Putri Amimah Nurfaidah; Restu Hilwani Azra; Rohmatul Laily Al Faiqoh (Institut Agama Islam Al-Hikmah Tuban, 2023)
Working in Islam is an effort to meet the needs of life; the main goal is to achieve mashlahah. However, if someone works in a conventional bank, is the law still permissible because bank interest is clearly forbidden in Islam? This study discusses the law of working in conventional banks from the perspective of Maqshid Syariah. This study uses qualitative methods with library research data collection techniques. The data used is secondary data in the form of data regarding the law of working in conventional banks from the perspective of Maqshid Syariah, obtained through journals, official documents, books, and articles related to the object of research. The study's findings concluded that, while working in a traditional bank is prohibited by law, when circumstances force people to fulfill their needs for the benefit of preserving life so that it is not threatened, the law is makruh on the condition that they continue to seek other jobs that are permitted by Islam.